2012
DOI: 10.1155/2012/736258
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Dietary Fiber and the Association of Fiber Intake with Childhood Obesity Risk (in 2–18 Year Olds) and Diabetes Risk of Adolescents 12–18 Year Olds: NHANES 2003–2006

Abstract: Increased fiber intake has been linked with lower risk of overweight and obesity in adults, but data are sparse for children. To address this issue, NHANES 2003–2006 data was used to evaluate (1) the food sources of fiber in children, (2) the dietary fiber density levels and risk of being classified as overweight/obese, and (3) the association between fiber intake level and impaired glucose metabolism in children. Analyses were restricted to the subsample of children with biological plausible diet reports (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 28 publications
2
44
0
3
Order By: Relevance
“…Such sensory results are positive and can favour the consumption of fibre amongst school age children, promoting healthier food consumption patterns. There is evidence indicating that the appropriate ingestion of fibre can reduce the risk of chronic diseases such as obesity and diabetes mellitus amongst children and adolescents (BRAUCHLA et al, 2012). Figure 1 shows the distribution of the tasters according to the hedonic scores awarded in the sensory test.…”
Section: Palavrasmentioning
confidence: 99%
“…Such sensory results are positive and can favour the consumption of fibre amongst school age children, promoting healthier food consumption patterns. There is evidence indicating that the appropriate ingestion of fibre can reduce the risk of chronic diseases such as obesity and diabetes mellitus amongst children and adolescents (BRAUCHLA et al, 2012). Figure 1 shows the distribution of the tasters according to the hedonic scores awarded in the sensory test.…”
Section: Palavrasmentioning
confidence: 99%
“…After grouping studies in accordance with outcomes of interest, one cross-sectional study (56) Fibre in childhoodinvestigating dietary fibre intake and folate status and one repeated publication (57) were excluded. Additionally, after performing adapted search commands on other databases and scanning the reference lists from included studies, two further cross-sectional studies (70,71) and five prospective cohort (64,(72)(73)(74)(75) studies were identified and included. In total, fifteen cross-sectional studies and eleven cohort studies were included in the present review.…”
Section: Search Strategymentioning
confidence: 99%
“…This was a large nationally representative sample (n 4667) with fibre consumption reported using 24 h recalls validated and screened to include only plausible dietary intake. Models were adjusted for common confounders but not for physical activity (70) . The association between adolescent fibre consumption and visceral fat was studied in a medium-size cohort (n 559) of adolescents (14-18 years).…”
Section: Cross-sectional Studiesmentioning
confidence: 99%
“…There is considerable evidence to support increased dietary fibre (DF) intakes with a reduced risk of obesity in adults (37) and whilst there are fewer data available for children, there are some studies clearly supporting this association (13,38,39) . DF intake and sources were estimated for Irish children (40)(41)(42) .…”
Section: Dietary Fibrementioning
confidence: 99%